A Decade of Short Videos for Foreign Language Teaching and Learning: A Review - Yidi Zhang; Margarida Lucas; Luís Pedro (MDPI AG, 2022)
This literature review focuses on the use of short videos for foreign language (FL) teaching and learning from 2013 to 2022, a research area that has been attracting growing attention. The results were classified according to three categories based on the scope of the short videos in research: (1) short videos as a medium, (2) short videos as an intervention, and (3) short videos as the central focus of studies. Such a categorization enabled us to determine that short videos have become an independent research term in the field of FL teaching and learning and to describe current trends in this field. The intrinsic characteristics of short videos in current educational and multimedia environments are discussed, namely, the reasons why short videos are used in the classroom, as well as the potential of short videos as a learning resource created by young students and as an open educational resource (OER). Finally, we consider the differences between short videos and traditional audiovisual resources to highlight their innovative contributions to FL teaching and learning.